2022
DOI: 10.5194/hess-2022-49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intertidal spring discharge to a coastal ecosystem and impacts of climate change on future groundwater temperature: A multi-method investigation

Abstract: Abstract. In inland settings, groundwater discharge is known to thermally modulate receiving surface water bodies and provide localized thermal refuges; however, the thermal influence of intertidal springs on coastal waters and the thermal sensitivity of these springs to climate change are not well studied. We addressed this knowledge gap with a field- and model-based study of a threatened coastal lagoon ecosystem in south-eastern Canada. We paired in-situ thermal and hydrologic monitoring with analyses of dro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The assumed similarity between groundwater discharge to streams and directly to the ocean (Figure 2) has testable implications for surface hydrology on the island. Previous local studies at two sites on the island (Danielescu et al, 2009; KarisAllen et al, 2022) indicated that a large portion and potentially the majority of freshwater groundwater discharge to the PEI coastline occurs in a focussed manner via springs, as opposed to diffuse discharge. While no quantitative data on the contribution of focussed groundwater discharge to streams is available on an island‐wide scale, studies have also reported the widespread presence of springs across the island (Brandon, 1966) and in individual watersheds (Francis, 1989).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The assumed similarity between groundwater discharge to streams and directly to the ocean (Figure 2) has testable implications for surface hydrology on the island. Previous local studies at two sites on the island (Danielescu et al, 2009; KarisAllen et al, 2022) indicated that a large portion and potentially the majority of freshwater groundwater discharge to the PEI coastline occurs in a focussed manner via springs, as opposed to diffuse discharge. While no quantitative data on the contribution of focussed groundwater discharge to streams is available on an island‐wide scale, studies have also reported the widespread presence of springs across the island (Brandon, 1966) and in individual watersheds (Francis, 1989).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the assumption detailed above, available hydrometric data between 2000 and 2019 for six PEI watersheds were analysed to evaluate the effects of precipitation event magnitude on groundwater discharge and nitrate loading to streams, and by extension, on SGD to coastal waters. Such SGD has been shown to significant in PEI coastal zones (e.g., Danielescu et al, 2009; KarisAllen et al, 2022; KarisAllen & Kurylyk, 2021). For example, 13% of the island's land area is closer to the coast that to any mapped (Government of PEI, 2011) stream (Figure 1b), favouring direct groundwater discharge to the coast from these areas.…”
Section: Study Site and Methodsmentioning
confidence: 99%
See 1 more Smart Citation